Research on robot manipulator uncalibrated visual serving under two-camera bi-axial parallel vision configuration. (24th April 2015) - Niu, Wang; Lang, Liu; Jing, Qiu; Wang, Datao
This article presents a two-camera bi-axial parallel vision configuration to realize robot manipulator uncalibrated visual serving. The intrinsic and extrinsic parameters of the camera and the model of robot manipulator are not known, as well as without real-time computes the inverse of image Jacobian when image-based dynamic control of a robot manipulator in this article. First, the proposed vision configuration is applied to transform the Cartesian posture information into the point and angle parameters in the two image planes. After that, a qualitative mathematical model was established which analyzes the relationship between the feature point and line of the robot manipulator in the Cartesian space and the corresponding specific point and angle in the image plane. In addition, the monotonic property of the point and line features in the mathematic model has been proved. Then, the controller was designed based on image and realized the five-degrees of freedom of the robot manipulator uncalibrated visual serving control in the simulation platform. Moreover, the Lyapunov theory was used to prove the global asymptotic stability of proposed method in the image plane. Finally, the proposed method was compared with the method of image Jacobian matrix in the actual platform experiment, and the comparative experiment results show the effectiveness of the robot manipulator uncalibrated visual serving under the proposed vision configuration.